TIPE KELOMPOK BATOBO DALAM AKTIVITAS PERTANIAN DI DESA KINALI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI (Studi Kasus Kelompok Batobo Lubuk Buayo) - Amrian, Firgani; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In the village of Kinali Batobo already has two forms or types, there are in a group Batobo of Lubuk Buayo in the village of Kinali. As for the purpose of the research is the first to find out how the type Group Batobo Lubuk Buayo Kinali village district Kuantan Mudik Kuantan Singingi regency. The second purpose to know how social system on type of group existing in the Group Batobo at Lubuk Buayo Kinali village district Kuantan Mudik Kuantan Singingi regency. The research includes the type of qualitative research, this research was conducted in the Dusun Tiga referred to as society with the Lubuk Buayo Kinali village district Kuantan Mudik Kuantan Singingi regency. The techniques used in the determination of the sampling and research is Purposive Sampling, data collection is done using the method of observation, interview. Then the data that has been collected in the form of words analyzed by qualitative descriptive analysis techniques. As for the findings in the study, namely the existing Batobo of Lubuk Buayo Kinali Village has two types of social groups. The first type, namely the Group of Batobo Kecil (Tobo Kenek) are included in the social group that is Called (gemeinschaft) rather belongs into the sellers because the type (gemeinschaft of place). Type into two Large Groups Batobo Besar (Tobo Godang) included in social groups, namely Patembayan (gesellscaft). Social systems on each type of group existing in the Group Batobo at Lubuk Buayo Kinali village already structured in each type of group batobo already has the position (status) and role (role) as seen from the existence of the Office of the Leader, the Treasurer, and members. As each Member of the Group has had the responsibility of batobo, obligations, and rights of which varies according to the position and role of each in the Group batobo.Keyword : Batobo, Group, System